Animated treatment: the method of art therapy used with children having communication problems - Liudmila Lebedeva (Social Welfare: Interdisciplinary Approach)
This article considers the author’s original technique of studying positive and negative aspects of social communication of children having selective communication problems. The art-technique presented in this article can be referred to as ‘expressive projective arttherapy’. The author’s specialized art-technique, utilizing self-made “finger-puppets” as the basis in a creative art-therapeutic session, are called “doll-therapeutic” sessions.